The Assessment of Body Mass Index as a Risk Factor for Chronic Periodontitis - Maham Khalid, Mehmil Aslam, Huma Tahir, Waheed Gul Shaikh, Marium Azfar, Nosheen Khawar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obesity is one of the highly emerging chronic disease. It is a major health concern now a days. The BMI of more than 35% of the adults were in the overweight category in 2008 but now the values are reported to be exceeded. The study aimed to assess the relationship between body mass index and chronic periodontitis. Study Design: It is a cross-sectional study with statistical approach, conducted at Karachi medical and dental college, Karachi Material and Methods: The study was conducted on 200 patients visited the dentist department of the hospital. The study was conducted for six month duration from Jan 2022 to June 2022. The ethical and review board of the hospital approved the study. Results: Among 200, 100 specimens belong to the normal weight category, 73 are overweight, and 27 are from the obese category. In each category, all the specimens are from similar age groups, but more males were present in the overweight and obese categories. Complete data analysis of these patients was performed. Then logistic regression analysis was performed, and it was predicted that periodontitis has a direct relation with the body mass index (BMI). About a 17% risk rate increases with an increase in each unit of BMI. Conclusion: This study supports the hypotheses of the association of obesity with periodontal issues. The body mass index is a factor for the assessment of different health risk factors. The body mass index and smoking are linked with periodontal issues. Smokers and obese people specifically young obese have a more critical periodontal state. Keywords: Body mass index and periodontitis.